A high-fat diet increases interleukin-3 and granulocyte colony-stimulating factor production by bone marrow cells and triggers bone marrow hyperplasia and neutrophilia in wistar rats. (April 2013) - do Carmo, Luciana Simão; Rogero, Marcelo Macedo; Paredes-Gamero, Edgar Julian; Nogueira-Pedro, Amanda; Xavier, Jose Guilherme; Cortez, Mayara; Borges, Maria Carolina; Fujii, Tatiane Mieko; Borelli, Primavera; Fock, Ricardo Ambrósio
It is well established that the excessive consumption of a high-fat diet (HFD) results in overweight, obesity and an increase in leptin concentrations, which triggers a chronic inflammatory condition that is associated with a high white blood cell count. Two-month-old male Wistar rats were fed a control (CON) diet or an HFD for 12 weeks. After this period, hemogram, myelogram and biochemical parameters were evaluated along with the cell cycle and the percentage of CD34 + cells in the bone marrow as well as cell proliferation and differentiation assays and the production of stem cell factor, interleukin 3 (IL-3), granulocyte colony-stimulating factor (G-CSF) and granulocyte macrophage colony-stimulating factor (GM-CSF). The HFD animals exhibited leukocytosis and neutrophilia with increased C-reactive protein, leptin, cholesterol and triglyceride concentrations. In the HFD group, the bone marrow revealed myeloid hyperplasia, especially of the granulocytic compartment with a higher percentage of CD34 + cells and a higher percentage of cells in the G2/S/M cell cycle phases. In addition, the HFD bone marrow cells had a higher capacity to proliferate and differentiate into granulocytic cells in an in vitro system and a higher capacity to produce IL-3 and G-CSF. These data led us to infer that the HFD induces leukocytosis and neutrophilia suggesting alterations in hematopoiesis system modulation.